A biological or a synthetic mesh in immediate breast reconstruction? A cohort-study of long-term Health related Quality of Life (HrQoL). Issue 10 (October 2019) - Hallberg, Håkan; Elander, Anna; Kölby, Lars; Hansson, Emma
Abstract: Objectives: Meshes/matrices are commonly used in immediate breast reconstruction. There are few studies comparing biological and synthetic meshes and it is unknown what type of mesh gives the best long-term results. The aim of this study was to compare long-term health-related quality of life (HrQoL) and patient satisfaction in implant-based immediate breast reconstruction with a biological mesh (Surgisis®) with that of patients reconstructed with a synthetic mesh (TIGR ® Matrix Surgical Mesh). Material and methods: Both cohorts were prospectively included and consecutively operated. Clinical data was collected. HrQoL was evaluated with EuroQoL-5 dimension – 3 levels questionnaire (EQ-5D-3L) and the Hospital Anxiety and Depression Scale (HADS) and the Breast-Q. Results and conclusion: Seventy-one patients were operated on in the biological group and 49 in the synthetic group. The response rates were 75 and 84 per cent, respectively. Mean follow-up time was 74 months and 23 months, respectively. There were no statistical differences in satisfaction and quality of life between the two groups. Complications and radiation seem to lead to a lower satisfaction. Our findings could indicate that biological and synthetic meshes give an equal long-term result as regards patients' perceived quality of life.